Reframing Reporting of Childhood Sexual Exploitation: Three journalists reflect. (28th May 2017) - Niblock, Sarah; Bindel, Julie
Abstract : This article explores three national and local journalists' experiences of reporting on child sexual exploitation by so-called "Asian street grooming gangs" in UK towns and cities, with a particular emphasis on journalists framing journalists. In response to coverage of a series of cases, journalists have been accused by academics, policymakers and rival media organizations of fixating on perpetrators' ethnicity and creating distorted, racist media frames. Few, if any, studies have garnered practitioners' perspectives on how framing occurs, so we interview three prominent journalists who have covered such cases in order to deepen our understanding of the processes and causative factors behind particular editorial angles. While offering only a snapshot view, our findings reveal these individual journalists to be caught at the nexus of a range of factors that impact upon their work, both internally and externally driven.